Callimachean Criticism in Anaximenes SH 45 and Choerilus of Iasos SH 333 - Marco Perale (Aitia)
This article traces the relics of Callimachean criticism in the testimonia to the work of Anaximenes of Lampsacus and Choerilus of Iasos, portrayed either as poet-sycophants or authors of bad quality poetry. It assesses the profile of Anaximenes as an epic writer and investigates the origin and dynamics of the confusion between Choerilus of Iasos and Choerilus of Samos in late Hellenistic and Imperial witnesses. It concludes that the negative judgment on Choerilus of Samos formulated by Istrus, a disciple of Callimachus, may have been wrongly transferred to Choerilus of Iasos and that it influenced later critics and writers’ perception of the latter.